Union Generals (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Union Generals; Maj.-General McClellan; Brig.-General Anderson; Maj.-General Fremont; Maj.-General Butler; Maj.-General Dix." These dates are approximate.